2018
DOI: 10.17557/tjfc.414856
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF HARVESTING DATES ON SOME AGRONOMIC AND QUALITY CHARACTERISTICS OF PEANUT (Arachis hypogaea L.) VARIETIES GROWN AS A MAIN CROP IN MEDITERRANEAN REGION (TURKEY)

Abstract: This study was conducted at the experimental area of the Department of Field Crops, Faculty of Agriculture, Cukurova University as a main crop in 2015 and 2016. The objective of this study was to determinate the effect of harvesting dates on some agronomic and quality characteristics of peanut (Arachis hypogaea L.) varieties grown as a main crop in Mediterranean region (Turkey). The experimental design was a split plot with three replications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 30 publications
(81 reference statements)
10
31
2
4
Order By: Relevance
“…Significant differences for palmitic, stearic and lignoceric acids percentage among the cultivars are attributable to the genetic makeup and place of their origin (Hassan et al, 2005). These results are in agreement with the findings of Dwivedi et al (2000), Anderson and Gorbet (2002), Ozcan and Seven (2003), Hassan et al (2005), Gulluoglu et al (2016), Sogut et al (2016) and Arioglu et al (2018),…”
Section: Saturated Fatty Acids Compositionsupporting
confidence: 93%
See 4 more Smart Citations
“…Significant differences for palmitic, stearic and lignoceric acids percentage among the cultivars are attributable to the genetic makeup and place of their origin (Hassan et al, 2005). These results are in agreement with the findings of Dwivedi et al (2000), Anderson and Gorbet (2002), Ozcan and Seven (2003), Hassan et al (2005), Gulluoglu et al (2016), Sogut et al (2016) and Arioglu et al (2018),…”
Section: Saturated Fatty Acids Compositionsupporting
confidence: 93%
“…The reason for the differences between the varieties for the iodine value was them having different oleic and linoleic acids content. These results are in agreement with the findings of How and Young (1983), Raheja et al (1987), Hashim et al (1993), Hinds (1995), Andersen and Gorbet (2002), Chaiyadee et al (2013), Chamberline et al (2014), Chowdhury et al (2015), Gulluoglu et al (2016) and Arioglu et al (2018) were indicated similar results.…”
Section: Oil Quality Valuessupporting
confidence: 92%
See 3 more Smart Citations